Influence of structural parameters on energy absorption characteristics of aluminum honeycomb anti-crawling device - CHEN Jiaming; ZHU Tao; XIAO Shoune; YANG Guangwu; YANG Bing (机车电传动)
In order to study the energy absorption and anti-climbing characteristics of aluminum honeycomb anti-climbing device of a certain type of subway vehicle, a reliable finite element model of equivalent aluminum honeycomb anti-climbing device was established by using the nonlinear finite element numerical simulation method. By studying the energy absorption characteristics of the aluminum honeycomb anti-climbing device under different structural parameters, the anti-climbing device was optimized. Finally, the optimized anti-climbing device was applied to the whole vehicle, and the collision condition of the 6-unit vehicle at 25 km/h was simulated. The simulation results show that increasing the thickness of the thin-walled shell greatly increases the initial peak force and the fluctuation of the impact force. The energy absorption effect of honeycomb blocks will be greatly improved by inserting baffles in series between several aluminum honeycomb blocks. It is one of the methods to induce stable and orderly deformation of anti-climbing device when opening induction holes in thin-walled shell. However, excessive number of induction holes will have a negative effect on energy absorption. Through the vehicle collision simulation, it is evaluated according to the relevant requirements of European railway standard EN 15227: 2020, which proves that the anti-climbing device has good energy absorption and anti-climbing performance, and provides a theoretical basis for the application of aluminum honeycomb anti-climbing device in subway vehicles.